2019
DOI: 10.1002/acr.23790
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Time and Transportation Walking Among Adults With and Without Arthritis in the United States, 2010

Abstract: Objective. Walking is a joint-friendly activity for adults with arthritis. The aim of this study was to estimate, among adults with arthritis, the prevalence of leisure and transportation walking overall (by arthritis status and by sociodemographic and health characteristics), the number of total minutes walking per week in each domain, and the distributions of walking bout length (i.e., short periods of activity) in minutes.Methods. Data were obtained from the 2010 National Health Interview Survey. Prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
1
7
3
Order By: Relevance
“…While this proportion is concerning given the health benefits associated with walking outdoors, 26,35,36 it is consistent with results obtained in the general population of older adults in Canada which estimate that 42% walk outdoors fewer than 3 days per week 37 . The specific nomenclature and questionnaire items used to assess aspects related to community ambulation have varied across studies; however, findings show consistency among the predictor variables of age, 24 walking difficulty, 38 chronic conditions, 38 and ratings of self‐rated health, 24 and inconsistencies regarding the significance of pain 23,24 . Unlike our results, gender was not significant in some previous multivariate analyses 23,24 .…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…While this proportion is concerning given the health benefits associated with walking outdoors, 26,35,36 it is consistent with results obtained in the general population of older adults in Canada which estimate that 42% walk outdoors fewer than 3 days per week 37 . The specific nomenclature and questionnaire items used to assess aspects related to community ambulation have varied across studies; however, findings show consistency among the predictor variables of age, 24 walking difficulty, 38 chronic conditions, 38 and ratings of self‐rated health, 24 and inconsistencies regarding the significance of pain 23,24 . Unlike our results, gender was not significant in some previous multivariate analyses 23,24 .…”
Section: Discussioncontrasting
confidence: 70%
“…People with OA walk fewer steps/d than otherwise healthy adults 22 . The 2010 USA National Health Interview Survey (n = 5565) determined that only 46% of respondents with arthritis reported walking for “fun, relaxation, exercise, or to walk the dog” for at least 10 minutes per week 23 . The unadjusted prevalence of leisure walking was lower in people with arthritis who were older, had lower levels of education, and more joint pain 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite arthritis being a cause of pain and disability, walking prevalence increased with increasing joint pain severity. A previous report on walking using national data described a similar finding, specifically for lower extremity joint pain (5). Collectively, these findings might signify that the presence of pain might not automatically preclude walking, other physical activities, and their associated benefits.…”
Section: Discussionsupporting
confidence: 67%
“…Research is now beginning to show how overlaying external contextual information, for example, location [24], onto objectively captured sensor data and patient-reported outcome data can help explain some of the observed variations and enable even more meaningful comparisons. Although the wearable sensor that we deployed does not allow for the direct capture of contextual information, it has been shown that by grouping concerted periods of walking ( bouts ) by length, some context can be inferred and enable comparisons of distinct behaviors over time and between individuals [16,25,26].…”
Section: Resultsmentioning
confidence: 99%